Analysis of Loading Change Effect to Boat Velocity on a 2.5GT Fishing FRP Boat with a Field Test - Syerly Klara; Faisal Mahmuddin; Muhammad Muas (LPPM ITK, 2018)
In order to determine the effect of load change to ship velocity on a 2.5 GT fishing boat, a field test is conducted in the present study. The boat model used in the field test is an actual size boat made from fiber reinforced plastic (FRP) material. The boat is powered by 2 (two) 15 HP direct drive engines each equipped with 3-bladed single screw propeller. Two loading cases are investigated and analyzed which are no load case and with load case. For each case, 4 (four) engine power variations are performed which are 25%, 50%, 75% and 100%. The main parameters measured are boat draught, engine power percentage, shaft revolution speed and boat velocity. From the field test, it is found that even though the propulsion performance increases larger loading and displacement, the increased boat resistance due to larger wetted surface make the boat velocity reduces.